2010
DOI: 10.1002/jsfa.3952
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolytic potential of anaerobic fungi (Piromycessp.) isolated from wild cattle and blue bulls in pure culture and effect of their addition onin vitrofermentation of wheat straw and methane emission by rumen fluid of buffaloes

Abstract: Wild cattle and blue bulls harbour some anaerobic fungal strains with strong capability to hydrolyse fibre. The fungal isolate CF1 has high potential for use as a microbial feed additive in buffaloes to improve digestibility of fibrous feeds without increasing methane emission per unit of digested feed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…Fungi from anaerobic environments (e.g. Piromyces, Neocallimastix [12], Orpinomyces, Anaeromyces [10]) are possessing fibrolytic activity and are able to enhance the digestibility of fibrous feeds as was documented for cattle [34], as well as wild-living herbivores like buffalo [35] and elephants [9]. Celluloses and hemicelluloses are forming plant cell walls, and their penetration and disintegration are the limiting steps in the anaerobic digestion of fibrous material, especially if they are embedded within the lignocellulose complex [36].…”
Section: Role Of Fungi In Biogas Reactorsmentioning
confidence: 99%
“…Fungi from anaerobic environments (e.g. Piromyces, Neocallimastix [12], Orpinomyces, Anaeromyces [10]) are possessing fibrolytic activity and are able to enhance the digestibility of fibrous feeds as was documented for cattle [34], as well as wild-living herbivores like buffalo [35] and elephants [9]. Celluloses and hemicelluloses are forming plant cell walls, and their penetration and disintegration are the limiting steps in the anaerobic digestion of fibrous material, especially if they are embedded within the lignocellulose complex [36].…”
Section: Role Of Fungi In Biogas Reactorsmentioning
confidence: 99%
“…Brookman et al ( 2000 ) identifi ed the formation of spores in the polycentric anaerobic gut fungi, which enhance their ability to survive and extend a possibility toward their use as direct-fed microbial (Tripathi et al 2007a ;Saxena et al 2010 ;Puniya et al 2014 ). Anaerobic fungi have been isolated from a number of ruminant and nonruminant herbivorous mammals (Ljungdahl 2008 ;Paul et al 2010 ). These contribute signifi cantly to overall metabolism of host with their high cellulolytic activity and play a greater role in degradation of lignifi ed plant tissues (Akin and Borneman 1990 ; Dey et al 2004 ;Thareja et al 2006 ;Sirohi et al 2012b ) with the help of a wide range of hydrolytic enzymes (Tripathi et al 2007b ;Shelke et al 2009 ;Nagpal et al 2009Nagpal et al , 2010Nagpal et al , 2011 including cellulases (Barichievich and Calza 1990 ), hemicellulases (Novotna et al 2010 ;Mountfort and Asher 1989 ), proteases (Michel et al 1993 ), amylases, amyloglycosidases (Paul et al 2004 ), feruloyl and p-coumaroyl esterases (Borneman et al 1990 ), various disaccharidases (Chen et al 1995 ), and pectinases (Kopecny and Hodrova 1995 ).…”
Section: Anaerobic Fungimentioning
confidence: 99%
“…Our earlier studies have indicated that some of the exogenous fungal isolates (isolated from different hosts) are not able to exert a positive effect on rumen fermentation, probably due to poor compatibility of the introduced fungi with the existing rumen microbes (Paul et al 2004(Paul et al , 2010. Our earlier studies have indicated that some of the exogenous fungal isolates (isolated from different hosts) are not able to exert a positive effect on rumen fermentation, probably due to poor compatibility of the introduced fungi with the existing rumen microbes (Paul et al 2004(Paul et al , 2010.…”
Section: Effect Of the Fungal Isolate On The In Vitro Digestion Of Whmentioning
confidence: 99%
“…Similarly, other studies have also indicated a positive effect of liquid cultures of anaerobic fungi (Dey et al 2004;Paul et al 2004;Tripathi et al 2007). Recently, it was shown that the addition of a specific fibrolytic fungi (isolated from the rumen of wild cattle) to the rumen fluid of buffalos resulted in a significant increase in fibre digestion, without increasing the methane emission per gram of truly digested wheat straw (Paul et al 2010). Hence, there is a need to isolate efficient strains of fungi, which produce higher levels of fibrolytic enzymes and can exert positive effects in co-culture with mixed rumen microbes of target hosts (domestic ruminants).…”
Section: Introductionmentioning
confidence: 99%